(untitled) (Research, Society and Development, 2020)
Objective: To describe the main microorganisms associated with respiratory infections, thus listing bacteria, viruses, fungi, protozoa and helminths. Methodology: This is a descriptive literature review with a qualitative approach, whose material selection was carried out using pre-established criteria, which corroborated the specificity of the search in the databases: SciELO, PubMed and the portal of CAPES journals, including a total of 42 contents, these, published between 2010 and 2020. Results and Discussion: Several are the organisms responsible for the involvement of respiratory tract infections, with bacteria as the main infectious agents in this sense, being acquired in the community, but with emphasis on its contamination, in the hospital environment. Viruses, in turn, correlate with the potential for morbidity and mortality in the diseases caused by them. In addition to these microorganisms, fungi, protozoa and helminths also have the ability to promote lung infections. Conclusion: In short, we can affirm the wide variety of microorganisms involved in the involvement of respiratory infections. In view of the physiological essentiality of the lungs, and the compromise that the infections result, often irreversibly or leaving sequelae, there is a need for studies aimed at developing therapies for the stabilization of compromised patients.